2003
DOI: 10.1128/aem.69.9.5648-5655.2003
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Formation and the Presence of the Intercellular Adhesion Locus ica among Staphylococci from Food and Food Processing Environments

Abstract: In clinical staphylococci, the presence of the ica genes and biofilm formation are considered important for virulence. Biofilm formation may also be of importance for survival and virulence in food-related staphylococci. In the present work, staphylococci from the food industry were found to differ greatly in their abilities to form biofilms on polystyrene. A total of 7 and 21 of 144 food-related strains were found to be strong and weak biofilm formers, respectively. Glucose and sodium chloride stimulated biof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
103
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(116 citation statements)
references
References 51 publications
11
103
0
2
Order By: Relevance
“…They found out that 50 times higher concentration of benzalkonium chloride and up to 600 times higher concentration of sodium hypochlorite caused a comparable decrease by 4 log of S. aureus cells when growing in biofilm in comparison with cells in suspension. Similar results were obtained by Møretrø et al (2003). The criterion of the necessary reduction by more than 4 log of cells in biofilm after 5 min in comparison with the initial concentration was used for the first time here; previous studies reported 3 log CFU as a sufficient reduction (Wirtanen 1995).…”
Section: Development Of Methodssupporting
confidence: 74%
“…They found out that 50 times higher concentration of benzalkonium chloride and up to 600 times higher concentration of sodium hypochlorite caused a comparable decrease by 4 log of S. aureus cells when growing in biofilm in comparison with cells in suspension. Similar results were obtained by Møretrø et al (2003). The criterion of the necessary reduction by more than 4 log of cells in biofilm after 5 min in comparison with the initial concentration was used for the first time here; previous studies reported 3 log CFU as a sufficient reduction (Wirtanen 1995).…”
Section: Development Of Methodssupporting
confidence: 74%
“…Nevertheless, half of the isolates were shown to produce biofilms in polystyrene plates. In this context, previous studies on biofilm formation on polystyrene surfaces have been found to be positively (Moretro et al 2003) or negatively (Rivas et al 2007) correlated with biofilm formation on stainless steel. The ability of the strains of this study to form biofilms onto stainless surfaces has yet to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Møretrø et al (2003) suggest that it is more appropriate to use the biofilm formation and not the presence or absence of the locus ica as one of the criteria for determining potentially virulent strains because biofilm formation on inert surfaces is highly sensitive to environmental and nutritional conditions, such as the presence of ethanol, iron, varying glucose and sodium chloride concentrations, among others. Kaiser et al (2013) developed a new CRA formula containing glucose, sodium chloride, and vancomycin, and they confirmed the capacity to detect biofilm in 210 S. epidermidis strains isolates, including only 76 (36.2%) icaAB gene-positives strains.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported higher frequency of distribution of the ica genes in Staphylococcus isolates from foods (Melo et al, 2013;Rumi et al, 2013;Ciftci et al, 2009;Rode et al, 2007;Møretrø et al, 2003).…”
Section: Introductionmentioning
confidence: 99%